PENGEMBANGAN MEDIA GIFT BOX BERBASIS MULTILITERASI PADA PEMBELAJARAN PENEMUAN DI KELAS VI SEKOLAH DASAR - Syifa Alivia Munawaroh; Encep Andriana; Sigit Setiawan (STKIP Persada Khatulistiwa Sintang, 2023)
Multiliteracy is an effort to help students improve various skills in the 21st century. Multiliteration can be collaborated with interactive learning media such as Gift Box. Gift Box learning media based on multiliteracy can help students understand the material, one of which is science material. The aim of this research is to find out the process of developing Gift Box media, find out the suitability of the media and find out students' responses after using multiliteracy-based Gift Box media which is integrated with the discovery model for class VI students. This research is Research & Development with the Lee & Owens development model, which consists of five stages, namely needs assessment and start-to-finish analysis, design, development, implementation and evaluation. Through the validation stage, the results obtained were that the appropriateness level in terms of media was 89.25% and was in the very appropriate category, in terms of material, 91.4% was in the very appropriate category, and in terms of language, 79% was in the appropriate category. Then, after the revision was carried out, the researchers conducted product trials on 28 class VI students and based on the student response questionnaire, the results were 93% in the very good category. It can be concluded that the Gift Box learning media based on multiliteracy in discovery learning is suitable for use and has received a very good response from students.